Sustainable development priorities and ensuring environmental sustainability: prospects for Uzbekistan - Seitova , Leila (GREEN ECONOMY AND DEVELOPMENT, 2024)
The article examines institutional-evolutionary concepts of sustainable development and their modern trends in the context of strategic management of regional economies. Theories and models of regional economic development based on the use of environmental factors are presented.